Regulating crystal surface of Cu2O distributed in graphene film to explore supercapacitive performance in liquid or gel electrolyte. (20th January 2023) - Ding, Yangbin; Zheng, Jiang; Gong, Baozhi; Ni, Haofei; Pan, Guoxiang; Tang, Peisong; Zhao, Jie
Highlights: Cu2 O with different facets were used to testify the shape-dependents relationship. These Cu2 O present different energy storage behaves in liquid and gel electrolyte. The underlying shape-dependent of the charge-storage mechanism was discussed. Abstract: The morphologies of transition metal oxides have a decisive impact on the performance of their applications. In this work, two kinds of Cu2 O nanocrystals with preferentially exposed 100 and 111 facets corresponding to Cu2 O nano-cube (Cu2 O NC) and Cu2 O nano-octahedron (Cu2 O NO) were designed. Then the different crystallographic Cu2 O nanocrystals were self-assembled to be flexible self-supporting Cu2 O and reduced graphene oxide films. By the comparison of the kinetic study of Cu2 O nanocrystal with two different exposure facets, the nanocrystal with preferentially exposed 111 behaves a larger proportion of surface-confined charging process, indicating faster ion adsorption and transferability. The specific capacity of an electrode with different exposed facets behaves as an obvious shape-dependence in the aqueous two-electrode system. In contrast with the hydrogel electrolyte system, the shape-dependence disappeared due to the sufficient ions adsorb in the slow ion diffusion electrolyte. Based on the intrinsic crystallographic plane of the cuprite Cu2 O, the charge-storage mechanism was elucidated. The so-called "crystallography-dependence" is relevant to the dangling bonds from the exposed 111 facets, which can act as active sites for electrochemical energy storage. Furthermore, the composite of Cu2 O NO/rGO shows a high capacity of 737.4 F g −1 . The Cu2 O NO/rGO film with exposure 111 facets demonstrated preferential adsorption of electrostatic charges on the planes and showed better charge-storage capability. In other words, there is a crystallography-dependent adsorption ability during energy storage. Graphical abstract: The Cu2 O NO/rGO film with exposure 111 facets demonstrated preferential adsorption of electrostatic charges on the planes and showed better charge-storage capability. Image, graphical abstract